2023
DOI: 10.3390/diagnostics13172805
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, Hemorrhagic Complications and CT Radiation Dose of Emergency External Ventricular Drain (EVD) Placement in Pediatric Patients: A 15-Year Retrospective Analysis

Robert Stahl,
Melvin D’Anastasi,
Robert Forbrig
et al.

Abstract: Purpose: To assess accuracy, the frequency of hemorrhagic complications and computed tomography (CT) radiation dose parameters in pediatric patients undergoing landmark-guided external ventricular drain (EVD) placement in an emergency setting. Methods: Retrospective analysis comprised 36 EVD placements with subsequent CT control scans in 29 patients (aged 0 to 17 years) in our university hospital from 2008 to 2022. The position of the EVD as well as the presence and extension of bleeding were classified accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(87 reference statements)
0
0
0
Order By: Relevance
“…Highly variable rates for EVD misplacements and hemorrhages have been reported earlier [ 1 , 9 , 13 , 14 , 28 , 29 ]. Anderson and colleagues noted a frequency of EVD misplacement of 8.8% in pediatric traumatic brain injury and a rate of asymptomatic hemorrhages of 17.6% [ 9 ], while Blaha et al reported 10% of asymptomatic hemorrhages [ 13 ] and Stahl et al 11.1% [ 29 ].…”
Section: Discussionmentioning
confidence: 82%
“…Highly variable rates for EVD misplacements and hemorrhages have been reported earlier [ 1 , 9 , 13 , 14 , 28 , 29 ]. Anderson and colleagues noted a frequency of EVD misplacement of 8.8% in pediatric traumatic brain injury and a rate of asymptomatic hemorrhages of 17.6% [ 9 ], while Blaha et al reported 10% of asymptomatic hemorrhages [ 13 ] and Stahl et al 11.1% [ 29 ].…”
Section: Discussionmentioning
confidence: 82%